2009
DOI: 10.1590/s0047-20852009000100001
|View full text |Cite
|
Sign up to set email alerts
|

Fatores associados à sintomatologia depressiva numa coorte urbana de idosos

Abstract: Palavras-chaveDepressão, capacidade funcional, idoso, mortalidade. rEsumo objetivo: Analisar a associação, em uma coorte urbana de idosos, entre sintomatologia depressiva e outros indicadores de capacidade funcional com a mortalidade após 15 anos de seguimento. métodos: Foram estudados os casos de 1.667 idosos (≥ 65 anos) residentes em Vila Clementino, na cidade de São Paulo, por meio de uma avaliação multidimensional da capacidade funcional e dos atestados de óbito referentes a mortes ocorridas entre 1991 (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1
31

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 17 publications
3
25
1
31
Order By: Relevance
“…In studies aimed at this population group, samples formed only of women are common, and when samples are mixed, the number of women frequently exceeds the number of men 4,7,11,13 . These findings reinforce the fact that on average women live longer than men and that more women attend specific programs specifically aimed at the elderly 2,[11][12][13][14][15]24 .…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…In studies aimed at this population group, samples formed only of women are common, and when samples are mixed, the number of women frequently exceeds the number of men 4,7,11,13 . These findings reinforce the fact that on average women live longer than men and that more women attend specific programs specifically aimed at the elderly 2,[11][12][13][14][15]24 .…”
Section: Discussionsupporting
confidence: 73%
“…It should also be noted that crosssectional studies based on associations should be evaluated carefully due to the great variability of methodological criteria 5,8,[12][13][14]24,30 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…37 The present study identified an association with some characteristics such as objectively and subjectively measured quality of sleep, the use of sleep medication and daytime dysfunction. However, this relationship was no longer found after adjustment of the predictive model, perhaps due to the limitations of the present study.…”
Section: Sleep Characteristicmentioning
confidence: 58%